A combined theoretical and experimental study on contact creep-induced clamping force relaxation of bolted joints at ambient temperature. (September 2022) - Li, Ying; Wang, Yuezhen; Liu, Zhifeng; Yang, Xiaodong; Zhang, Caixia; Cheng, Yanhong
Abstract: The clamping force relaxation of bolted joints caused by contact creep at ambient temperature has a significant impact on the service performance of offshore structures, which may increase their vulnerability to additional non-typical loads. Maxwell and Kelvin architectures are introduced to analyze the creep displacement of rough surfaces in contact. Subsequently, a theoretical model is established to characterize the functional relationship between contact creep and clamping force relaxation. The model parameters are obtained from a compression creep experiment. An experimental device is developed to validate the proposed model. The experimental results show a good agreement with theoretical calculations. In addition, the influences of bolt preload and surface topography on the clamping force relaxation are investigated quantitatively, and find that the clamping force relaxation is proportional to the surface roughness. Thus, controlling surface topography and bolt preload could be an effective way to improve performance of bolted joints for steel structures. Highlights: Contact creep displacement at ambient-temperature creep is analyzed. The functional relationship between creep and relaxation is characterized. A novel experimental method is proposed to obtain the model parameters. The clamping force relaxation decreases with the increase of surface roughness.